Analysis of the coding-complete genomic sequence of groundnut ringspot virus suggests a common ancestor with tomato chlorotic spot virus - De Breuil, Soledad; Cañizares Sales, Joaquin; Blanca Postigo, Jose Miguel; Bejerman, Nicolas Esteban; Trucco, Veronica Milagros; Giolitti, Fabian; Ziarsolo, Peio; Lenardon, Sergio Luis (2017)
Groundnut ringspot virus (GRSV) and tomato chlorotic spot virus (TCSV) share biological and serological properties, so their identification is carried out by molecular methods. Their genomes consist of three segmented RNAs: L, M and S. The finding of a reassortant between these two viruses may complicate correct virus identification and requires the characterization of the complete genome.